Mid to late Holocene environmental change and human impact: A view from Central China. (1st November 2019) - Lu, Fengyan; Dodson, John; Zhang, Wenchao; Yan, Hong
Abstract: Dajiuhu, a rare peatland in Central China, has attracted several studies. There are differences in the interpretations of its Holocene record, and little has been written on landscape transformation by human impact. A 6100 yr palynologic record, together with TOC and charcoal data, from Dajiuhu peatland is assessed to provide a new perspective on mid-late Holocene environmental change and human activity. We found that wetland herb pollen is a sensitive marker of effective precipitation, and the ratio of evergreen and deciduous tree pollen can be a proxy for temperature variability at the site. A mixed evergreen and deciduous forest dominates the record. Peak warming was at 2900 cal yr BP and cool events occurred around 5100, 4100 and 2700 cal yr BP. The cooling at 5100 and 2700 cal yr BP may be related to decreased solar activity. There was a long-term drying trend punctuated by episodic droughts around 3000 to 2800 cal yr BP and following 1500 cal yr BP; we argue that these relate to the southward retreat of the ITCZ. A low level of regional fires was present as background. At 800 cal yr BP there were declines in forest taxa, increases in ferns, herbs, burning and inorganic inputs into the sediment; these signal sustained human impact in the area. The relatively late human impact is probably related to the rugged mountain landscape and river systems prone to frequent flooding, or may be due to a late expansion in human population and land resource pressures at Dajiuhu. Highlights: A mixed evergreen deciduous forest is present throughout the record. Both temperature and precipitation showed more variability from 3600 yr BP. Abrupt cooling events at 5100 and 2700 a BP may relate to decreased solar activity. A long-term drying trend punctuated by episodic droughts may relate to ITCZ shifts. The most obvious landscape transformation caused by human impact was around 800 yr BP.